2019
DOI: 10.3390/ijms20092123
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Models of Brugada syndrome

Abstract: Brugada syndrome is an inherited, rare cardiac arrhythmogenic disease, associated with sudden cardiac death. It accounts for up to 20% of sudden deaths in patients without structural cardiac abnormalities. The majority of mutations involve the cardiac sodium channel gene SCN5A and give rise to classical abnormal electrocardiogram with ST segment elevation in the right precordial leads V1 to V3 and a predisposition to ventricular fibrillation. The pathophysiological mechanisms of Brugada syndrome have been inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 88 publications
0
29
0
Order By: Relevance
“…In epicardial myocytes in the RVOT, the loss-of-dome AP followed by marked shortening of APD, i.e., repolarization abnormality 7,26 , is considered to be one of the mechanisms of coved-type ST-segment elevation (Brugada-type ECG) 2,6 . One of the factors causing the loss-of-dome is thought to be the ventricular gradient of I to through the RV wall, as well as endogenously heterogeneous I to in the RV epicardial layers 7,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In epicardial myocytes in the RVOT, the loss-of-dome AP followed by marked shortening of APD, i.e., repolarization abnormality 7,26 , is considered to be one of the mechanisms of coved-type ST-segment elevation (Brugada-type ECG) 2,6 . One of the factors causing the loss-of-dome is thought to be the ventricular gradient of I to through the RV wall, as well as endogenously heterogeneous I to in the RV epicardial layers 7,26 .…”
Section: Discussionmentioning
confidence: 99%
“…BrS is characterized by the electrocardiograms with both a right bundle-branch block pattern and ST-segment elevation in the right precordial leads (V 1 –V 3 ) and by the higher incidence of sudden cardiac death due to ventricular tachycardia/fibrillation (VT/VF) 5 , 6 . It is commonly believed that VT/VF is elicited by the closely coupled premature ventricular contractions via the phase-2 reentry (P2R) mechanism 6 . This mechanism is that APs with phase-2 dome in some sites of the tissue re-excite neighboring repolarized sites via electrotonic interaction to evoke an additional conductive AP (triggered activity) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, hiPSCs have been increasingly employed to elucidate pathophysiological mechanisms of various cardiovascular diseases (reviewed in Giacomelli et al, 2017) [41]. They have been shown to be effective for phenotype and drug response studies in diseases with genetic mutations such as long QT syndrome [42], short QT syndrome [43], catecholaminergic polymorphic ventricular tachycardia (CPVT) [44], atrial fibrillation [45], dilated cardiomyopathy (DCM) as well as hypertrophic cardiomyopathy (HCM) [5,46], arrhythmogenic right ventricular dysplasia (ARVD) [47], Brugada syndrome [48], Timothy syndrome [49], and Duchenne muscular dystrophy [50]. Another area of application of hiPSC-based technologies has been the modelling of diseases with early-onset symptoms, in particular cardiometabolic diseases (Fabry's disease [51], Pompe disease [52], Danon disease [53], Barth syndrome [54]).…”
Section: Approaches To Model Heart Failure In a Dish Using Hipsc-cmsmentioning
confidence: 99%
“…Besides low cardiac output due to reduced contractility, patients with heart failure are threatened by malignant arrhythmias like ventricular tachycardia or fibrillation. As mentioned above, several studies have been reported using hiPSC-CMs to model channelopathies, namely long QT [42], short QT [43], and Brugada syndrome [48], but also arrhythmic diseases like CPVT [44].…”
Section: Analysis Of Hipsc-cm Modelsmentioning
confidence: 99%
“…BrS is characterized by the ECGs with both a right bundle-branch block pattern and ST-segment elevation in the right precordial leads (V 1 -V 3 ) and by the higher incidence of sudden cardiac death due to ventricular tachycardia/fibrillation (VT/VF) (4,5). It is commonly believed that VT/VF is elicited by the closely coupled premature ventricular contractions via the phase-2 reentry (P2R) mechanism (6).…”
Section: Introductionmentioning
confidence: 99%